YIELD MARKETABILITY OF EARLY POTATO VARIETIES DEPENDING ON THE DURATION OF GERMINATION - Myalkovsky , R. O; Bezvikonnyi , P.V. (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
The article considers the influence of the duration of seed germination on the yield and marketability of potato tubers in the conditions of the Right-Bank Forest Steppe of Ukraine. Phenological observations, biometric and physiological-biochemical studies were carried out according to the methods of L. Bondarenko, K.I. Yakovenko. The material of the investigations was the soil of the experimental field - chernozem typical vyluzhenny, slightly humus, medium loamy in forest-like loam. As the object of research used tubers of varieties: Lishchyna, Skarbnytsya. The studies were carried out in the experimental field of the Podil'e Training and Production Center of the Podolsky State Agrarian and Technical University during 2016-2018. It is established that the yield of large tubers (more than 80 g) increases depending on the duration of germination of the planting material. In variants (germinated for 20, 30 days) the number of large tubers (weighing> 80 g) in the variety Lishchyna is 35.4-37.0%, and in the control 34.2%; in Skarbnytsya variety - 37.5-39.9% and in the control variant without germination - 35.8%. The increase in the number of large tubers (more than 80 g) is mainly due to the reduction of small tubers of the crop. So, germination of seed before planting for 30 days, helps to reduce small tubers in Lishchyna variety - 16.7% (control - 20.3%), in Skarbnytsya variety - 16.6% (control 19.8%). Thirty-day germination contributes to increasing the marketability of potato tubers of the Lishchyna variety up to 83.8% and obtaining a marketable yield of 1 ha 20.5 t / ha, of the Skarbnytsya crop 83.3% of the yield and obtaining of 1 ha 21.5 t / ha. Marketability of tubers in relation to control increases by 27.3 and 26.5% in accordance. Thus, germination of tubers before planting promotes rapid growth of the leaf surface, increases the yield and marketability of early potatoes. Specifically, by germinating seed material for 30 days before planting, the yield of tubers of early potato Lishchyna variety - 24.6 c / ha, Skarbnytsya variety - 25.8 c / ha with high marketability of 127.2 and 126.4% can be achieved, in accordance.